The influence of p90RSK on FAK-dependent signalling in human oesophageal squamous carcinoma cells - Lachenicht, Candice (My University, 2017)
The focal adhesion kinase or FAK plays an important role in detecting and transducing signals that are generated by cell-substrate attachment (Focal adhesions). When these pathways are activated under atypical conditions they may promote metastasis, uncontrolled proliferation and a chemo-resistant phenotype. However the mechanisms by which this protein is activated ectopically in human oesophageal squamous cell carcinomas cell lines (HOSCC) is unknown. In the current study it was hypothesised that the p90 ribosomal S6 kinase, a key member of multiple pro-survival pathways (activator of the Y-box binding protein-1), activates FAK. RSK may promote FAK activation directly, from its location at the plasma membrane, or it may modulate FAK activation indirectly via the regulation of one of its substrates. RSK inhibits the activation of the glycogen synthase kinase 3β (GSK3β) by phosphorylation at Ser9. GSK3β also localises at focal adhesions and may therefore play a role in mediating FAK activity. To ascertain the role RSK plays in FAK activation, 3 inhibition studies were performed. In the first assay, RSK was specifically inhibited within HOSCC and the levels of active FAK monitored (two different environmental conditions). FAK activation was monitored by detecting the auto-phosphorylation of FAK at Tyr397. A GSK3β inhibition assay was then performed in which GSK3β was specifically inhibited and the levels of active FAK monitored. Lastly, a dual inhibition assay was performed where both RSK and GSK3β were inhibited simultaneously and the levels of active FAK monitored. The overall net changes in the phospho-protein profile indicated that all of the HOSCC cells had distinct cellular responses to the three inhibitor combinations. However RSK did not appear to activate/inhibit FAK activity directly, in most of the HOSCC cells, but rather modulated FAK activation through the inhibition of GSK3β. The effects the RSK/GSK3β pathway had on FAK activation was partially dependent on the HOSCC cells containing active levels of PTEN. Interestingly, the inhibition of both GSK3β and RSK reduced the levels of active FAK in 3 of the 5 HOSCC cell lines, indicating that this might be a good anti-cancer therapeutic. RSK appeared to play a more context specific role in FAK activation within the HOSCC cells suggesting that the grading system for moderately differentiated carcinomas needs to be improved. This paper also highlights the importance of studying the effects the microenvironment has on neoplasmic transformation as varied environmental conditions, during the RSK inhibition studies, drastically impacted the effects the RSK inhibitor had on FAK activation.
Research dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Science. 28th May 2017.
Keywords: Esophagus--Cancer; Molecular biology; Cell differentiation; Squamous cell carcinoma